Physical analysis of building materials with soil. (December 2020) - Jaramillo, H Y; Gómez, J A; Martinez, C A
Abstract: Industrialization in construction has allowed the use of materials such as concrete and steel, these being essential for the construction of large buildings and structures, however, in some vulnerable areas, using this type of techniques and materials represents a high cost, due to which the traditional or vernacular architecture is a sustainable alternative. This research carries out a physical analysis of the materials used in the constructions on land that are developed in the municipality of Ocana, Norte de Santander, Colombia. The results obtained indicate that the soil used in the analyzed structures has a maximum density of 1.41 g/cm3 with a humidity percentage of 32.55%; likewise, in natural condition these soils have a liquid limit of 67.85 a limit plastic of 45.72 and a plasticity index of 22.13. In other words, the soil has characteristic plastic characteristics of a fine soil. This corresponds to the granulometric classification of the soil, which corresponds to a high plasticity Silt, which has sands with diameters between 395 μm and 76.1 μm. It also has a specific gravity of 2.65 g/cm 3 .